If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 2y + -3 = 7y + 4 + -4y Reorder the terms: 4 + -3 + 2y = 7y + 4 + -4y Combine like terms: 4 + -3 = 1 1 + 2y = 7y + 4 + -4y Reorder the terms: 1 + 2y = 4 + 7y + -4y Combine like terms: 7y + -4y = 3y 1 + 2y = 4 + 3y Solving 1 + 2y = 4 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 1 + 2y + -3y = 4 + 3y + -3y Combine like terms: 2y + -3y = -1y 1 + -1y = 4 + 3y + -3y Combine like terms: 3y + -3y = 0 1 + -1y = 4 + 0 1 + -1y = 4 Add '-1' to each side of the equation. 1 + -1 + -1y = 4 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = 4 + -1 -1y = 4 + -1 Combine like terms: 4 + -1 = 3 -1y = 3 Divide each side by '-1'. y = -3 Simplifying y = -3
| p+p+p=180 | | 0.83x-4=1.5x+2 | | 0.5x+5=0.75x+1 | | 9+2x-8=5x+7+2x | | 15b^2+19b+6=0 | | 0.4x+3.2=2.5x-1 | | 2y^3-2.80(5.89+3y)=23.87-8.40y | | 25=5x+30 | | 1.5x+2=0.25x+7 | | (-10)=5x^2-1 | | 5x^2(5x^2)+5x^2(5)+(5)(5x^2)+(5)(5)= | | f(x)=x^2-x+5 | | log[5](3t+2)-log[5]t=log[5]4 | | 10x+x*3=0 | | 2346+3456= | | 19182x=192 | | 3.4x+52.6=24.8-10.5x | | 3(6y-5)-(7y+2)= | | 14x+4+5x+5=180 | | r^2+8r-2=0 | | 5x+5=14x+4 | | c^2-10c+6=0 | | .25(2b-12)+b^2=.5b+22 | | 4+3t-1=8t+7-4t | | xy+4x+6y+24= | | x^2-5/2x-24 | | 12y^4-10y^2= | | x^2+4x-7x-28= | | x-(30/100)x=124 | | 5x(3x+2)+3x+2= | | bd=c+ba | | x(y+2)-17(y+2)= |